Transcranial Doppler Screening In Children with Sickle Cell Disease of South Gujarat Population - Ekta Jayantkumar Desai; Dhagash Patel; Mona Digantkumar Shastri; Sunny Mishra (Medsci Publications, 2021)
Background: TCD (Transcranial Doppler) is a well-established study to predict Cerebrovascular stroke in SCD (Sickle cell disease). We aim to establish baseline TCD findings in Indian children with SCD and compare the results with the available STOP (Stroke prevention trial in Sickle Cell Anemia) protocol. We would also compare TCD findings in homozygous sickle cell disease and heterozygous sickle cell trait. Material and Methods: Seventy nine children with SCD were included in this study for one year period. TCD was performed and TAMMV (time-averaged maximum mean) velocity in the middle cerebral, anterior cerebral, posterior cerebral and internal carotid arteries was measured. Children were divided into two groups. Group I (56 homozygos-70.88%) and group II (23 heterozygos-29.11%). Results: In group I, 50 children fall in normal range with average TAMM velocity of 127.59 ± 17.48 cm/s. There was 1 (1.78%) abnormal result and 5 (8.9%) conditional results in group I. All results were normal in group II with average TAMM velocity of 116.33 ± 12.412 cm/sec. Middle cerebral artery was the only affected vessels amongst all. Conclusions: In our study, there was low prevalence of abnormal TCD results as compared to STOP protocol. The difference was significant in TAMM velocity between two groups, with all children being within normal range in group II. Result of this study differs from previous studies, done in western countries probably due to difference in haplotype.